Tatterhood and other tales : Stories of magic and adventure - Phelps, Ethel Johnston; Baldwin-Ford, Pamela (Old Westbury, N.Y. : The Feminist Press, 1978)
A collection of traditional tales from Norway, England, China, and many other countries.
Suggested reading : p. 165
Keywords: Tales; Folklore; Fairy tales